Root Cause Analysis on Production Target Achievement Failure of CV. Bungsu Pratama Mandiri (The Indonesian Journal of Business Administration, 2021)
CV. Bungsu Pratama Mandiri is one of Micro, Small and Medium Enterprises (UMKM) from Bandung which produces various local brands such as Brodo, Donatello, Winshor, etc. The role of this company in the business of various shoe brands is as a shoe maker. Since 2016, the company started producing Brodo brand shoes with boots and machetes (parang) which are still ongoing today. Brodo is the largest buyer of CV. Bungsu Pratama Mandiri which has the highest number of orders compared to other brands that cooperate with the company to produce its shoes. The problem is the company failing to achieve the production target as requested by the buyer. So that the delivery of finished goods to the buyer's warehouse is delayed, this happens to all buyers such as Brodo, Donatello, and Winshor, where they often run out of stock of goods. Based on these conditions, this study aims to identify the source of the causes that resulted in failure to achieve production targets. And then provide recommendations to CV. Brodo Pratama Mandiri to solve the problem. Because Brodo is the largest buyer for the company, the authors make Brodo the focus of research. Based on the analysis results on the fishbone diagram and 5 why's analysis, there are 3 things that are the root causes of production target achievement failure. The three things are; no contract agreement, didn't know how to measure the workload, no activity mapping running on the production floor. The search for solutions is carried out using the combination of Value Focused Thinking (VFT) and Systematic Inventive Thinking (SIT) method to eliminate the identified root causes. VFT used to identify what variables are contained in the problem, and SIT used to to find the alternatives solution. Alternative solutions proposed to overcome the problem of failure to achieve production targets are; make work agreement, provide time study training, standardize the working hour, create a Gantt Chart to map activities on the production floor. Keywords: production target achievement failure, fishbone diagram, 5 Why’s Analysis, Value Focused Thinking (VFT), Systematic Inventive thinking (SIT)